A Proteomic Analysis Using an Animal Model for Hyperlipidemia-related Erectile Dysfunction - Hwang, Y.-G.; Lee, H.; Lee, S.; Chung, H. K.; Kang, K. K.; Kim, S. H. (Drug Research, 2014)
To investigate the pathogenesis of hyperlipidemia-related erectile dysfunction and the effects of DA-8159, a new phosphodiesterase-5 inhibitor, on protein expression, we performed a proteomic analysis of differentially expressed proteins in the corpus cavernosum of hyperlipidemic rats by two-dimensional electrophoresis-mass spectrometry. Rats were fed high-cholesterol diet and treated with 5 mg·kg−1·day−1 DA-8159 concurrently. After 5 months apparent hyperlipidemia and significantly decreased maximal intra-cavernous pressure were observed in the control group with the alteration of 8 proteins, which were restored by DA-8159 treatment. The proteins whose levels decreased >2-fold and attenuated by DA-8 159 were determined alcohol dehydrogenase, aldolase A, annexin 1, and tropomyosin-rat, whereas proteins increased>2-fold and recovered by DA-8159 were found to be aldehyde dehydrogenase complex, guanine deaminase, creatine kinase-B, and phosphoglycerate mutase type B subunit.
Keywords: cholesterol diet; two-dimensional electrophoresis; mass spectrometry; phosphodiesterase-5 inhibitor